BENDING OF CIRCULAR PLATES CONFINING AND INCOMPRESSIBLE LIQUID. - Kerr,Arnold D. (1966)
Frozen potholes subjected to lateral loads suggest the study of the effect of the confined incompressible liquid upon the behavior of the covering ice plate. Since, for loads of short duration, no creep is expected, the plate may be assumed to behave elastically. The method of solution is described and two examples are treated in detail. A comparison of numerical results shows the strong effect of the confined incompressible liquid upon the deflections and stresses of the plate. (Author)